Keeping Tradition in The Overseas Land: The Tariqa Shattariyya in Ulakan-Minangkabau Society in Medan City - Bakar, Abu (Al-Fikru: Jurnal Ilmiah, 2023)
This article describes the Tariqa Shattariyya, which has undergone acculturation into a tradition of the Ulakan-Minangkabau people in Medan City. The Tariqa Shattariyya for the Ulakan people is practiced in the homeland and maintained in the overseas realm. This article focuses on the research question of how the Tariqa Shattariyya in the Ulakan people in Medan City. The research findings explain that the Tariqa Shattariyya in Medan City continues to be maintained and maintained through the community’s religious tradition, namely the basapa tradition; every year, the Ulakan people plans to go on a pilgrimage to the tomb of the Tariqa Shattariyya teachings in Ulakan. The tradition of the Prophet’s birthday is by reading the book of sharafal anam; in commemoration of this birthday, the Tuanku, Labai, and the society gather at the surau. This tradition is very different from the tradition of the Prophet’s birthday in general. The tradition of calling urang siak, this urang siak is a person who is an expert in reading prayers, tahlil and fardu kifayya. Finally, this article concludes that the Tariqa Shattariyya is the identity of the Ulakan people in Medan City